Spatial Analysis of Landslide Prone Areas in Tidore Island Indonesia - Latue, Theochrasia; Latue, Philia C; Rakuasa, Heinrich (Journal of Geographical Sciences and Education, 2023)
The topographic condition of Tidore Island, where 50% of the area is on a steep slope, makes Tidore Island prone to landslides during the rainy season. This research aims to spatially identify landslide prone areas in Tidore Island using slope morphology method. SMORPH method is conducted by identifying and classifying potential landslide areas based on slope shape and slope angle matrix. The result of this study shows that high landslide potential area is 2,569.42 ha, medium potential area is 3,296.99 ha, low potential area is 4,778.46 ha, and very low potential area is 1,126.55 ha. Among the sub-districts in Tidore Island, North Tidore has the largest presentation area of 892.48 ha. It can be concluded that areas with steep slopes and convex or concave slope shapes have higher landslide potential. The findings of this research are expected to help local government in future spatial planning efforts for landslide mitigation.